2021
DOI: 10.1177/13623613211035229
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural context and autistics’ quality of life: A comparison between Québec and France

Abstract: Quality of life is important for the development and evaluation of interventions for autistic people. It is a multidimensional concept, anchored in a sociocultural context and based on a person’s subjective assessment of their life. The aim of this study is to examine whether the determinants of perceived quality of life vary by country (or culture) by comparing two groups of French-speaking autistic adults ( n = 430), one in France and the other in Québec (Canada). A cross-sectional survey was conducted to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
(100 reference statements)
2
7
0
Order By: Relevance
“…Grappling with a disconnect between perceptions of how they view their autistic identity and societal misconceptions is found across the autistic life span. A recent study on the quality of life of autistic adults showed that the most important predictor of quality of life in this population was the experience of social stigmatization—reportedly even more impactful than autistic traits, employment status, or biological sex (Caron et al, 2021). Hence, shifting narratives that promote the stigmatization of autistic individuals (Den Houting et al, 2021), while simultaneous fostering supportive communities that embrace the multitude of autistic identities, are imperative for the well-being of autistic youth and adults.…”
Section: Autistic Identitiesmentioning
confidence: 99%
“…Grappling with a disconnect between perceptions of how they view their autistic identity and societal misconceptions is found across the autistic life span. A recent study on the quality of life of autistic adults showed that the most important predictor of quality of life in this population was the experience of social stigmatization—reportedly even more impactful than autistic traits, employment status, or biological sex (Caron et al, 2021). Hence, shifting narratives that promote the stigmatization of autistic individuals (Den Houting et al, 2021), while simultaneous fostering supportive communities that embrace the multitude of autistic identities, are imperative for the well-being of autistic youth and adults.…”
Section: Autistic Identitiesmentioning
confidence: 99%
“…134 The lower social standing of stigmatised minority groups is believed to lead to exposure to more stressful life events, alongside fewer resources to manage these events. 3 Autistic people have reported a wide range of stressors common to minority groups, including victimisation, violence, discrimination, rejection and felt stigma 3,35,135 , which predicted heightened psychological distress, reduced wellbeing 3 and reduced quality of life. 135 Similarly, only 7% of autistic adults felt accepted as an autistic person within society, with feelings of acceptance protecting against depression.…”
Section: Moderating Factorsmentioning
confidence: 99%
“…3 Autistic people have reported a wide range of stressors common to minority groups, including victimisation, violence, discrimination, rejection and felt stigma 3,35,135 , which predicted heightened psychological distress, reduced wellbeing 3 and reduced quality of life. 135 Similarly, only 7% of autistic adults felt accepted as an autistic person within society, with feelings of acceptance protecting against depression. 136 These findings are particularly relevant given the high prevalence of co-occurring mental health conditions in autistic people.…”
Section: Moderating Factorsmentioning
confidence: 99%
“…However, our data showed no correlation between the time since diagnosis and attitudes towards autism. Fifth, cultural setting may play a role because attitudes towards autism, the quality of life of autistic people and therapeutic approaches may vary by country (Caron et al, 2021). This study was conducted in Poland.…”
Section: Discussionmentioning
confidence: 99%